Torus mandibular Mandibularis Tori - M Dutto; RE Achenbach (Asociación Argentina de Dermatología, 2012)
Presentamos un caso de torus mandibular, lobular; entidad frecuente en la consulta odontológica pero poco conocida o comunicada en la literatura dermatológica. Enfatizamos la necesidad de familiarizarse con este tipo de exostosis ósea, para no incurrir en estudios innecesarios al pensar en neoplasias malignas del piso de la boca. A case of mandibularis tori, lobular type is reported. Tori appear more frequently during middle age; it is well known in the dental literature but rarely mentioned in the dermatological one. Certain prevalence with respect certain ethnic groups has been observed, its surgical elimination are due mainly to prosthodontics reasons. The importance in the diagnosis is emphasized.